Inculcation of higher order thinking skills (HOTS) in Arabic language teaching at Malaysian primary schools - Mohd Yusri Kamarudin; Nik Mohd Rahimi Nik Yusoff; Hamidah Yamat@Ahmad; Kamarulzaman Abdul Ghani (Scientific Research Publishing, 2016)
This study was aimed at identifying activities and teachers’ role in inculcating Higher Order Thinking Skills (HOTS). A total of 30 teachers among main trainers of the Arabic language (j-Qaf) in primary schools in Malacca were selected as the respondents for the study. Data was collected via a questionnaire developed based on the checklist for teaching creativity and critical thinking (Teacher Checklist for Creative and Critical Thinking Instruction-TC-C2TI) and analysed for frequency, percentage, and mean. Findings have shown that the teachers provide support for exploration activities and conduct experiments among their students. Support is often given by providing opportunities for the students to think, learn, and study.